Influence of the Axial Machining Length on Microgeometrical Deviations of Horizontally Dry-Turned UNS A97075 Al-Zn Alloy - Sevilla-Hurtado, Lorenzo; Trujillo-Vilches, Francisco Javier; Marcos Bárcena, Mariano (Universidad de Zaragoza, 2013)
The arithmetical average roughness, Ra, is widely used to evaluate the quality of surface finish in machining parts. Its value depends on cutting parameters: cutting speed, feed and cutting depth. It is necessary to optimize the value of these parameters to achieve the desired quality, especially in the absence of cutting fluids. In this work, a study of the superficial quality of test bars, turned in dry, of an AL-Zn UNS A97075 alloy is presented. The value of Ra has been analyzed along the axial machining length for a series of test-pieces obtained under different combinations of cutting parameters values. The obtained results confirm that feed has the biggest influence. Finally, a potential relationship between Ra, cutting parameters and machining time has been obtained. This relationship allows predicting the behavior of Ra in the range of cutting parameters considered, along the machining time.
Keywords: Corte; Dry-Turning; UNS A97075; Roughness; Cutting Parameters